A PL1 family pectate lyase CP966_RS08110 gene was the pathogenic factor of Streptomyces galilaeus 5T-1 causing potato common scab - Zhang, Cuiwen; Yang, Chengde; Jin, Mengjun; Feng, Zhonghong; Osei, Richard; Cai, Fengfeng; Ma, Ting; Wang, Yidan (Frontiers in Microbiology, 2024)
Pectate lyases (PL), as important polysaccharide lyases, play an important role in the infection of host plants by pathogenic. A previous study found that the PL gene CP966_RS08110 was up-regulated in the interaction between Streptomyces galilaeus 5T-1 and potatoes. In this study, S. galilaeus 5T-1 was used as the study object, and its gene function was investigated using bioinformatics analysis, prokaryotic expression, and CRISPR-Cas9 technology. The previous results showed that the pectate lyase CP966_RS08110 gene of Streptomyces galilaeus 5T-1 was up-regulated in the pathogenic process. In this study, the CP966_RS08110 gene was cloned from the genomic DNA of S. galilaeus 5T-1. It encoded for a 415-residue protein with a complete PL-6 superfamily domain and Pec_lyase_C domain, which belongs to the PL1 family. The soluble protein encoded by CP966_RS08110 was obtained successfully, which has high pathogenicity after inoculating healthy potatoes. The mutant strain △PL5T-1 with CP966_RS08110 gene deletion was successfully obtained, and its colony morphology and pigment were not significantly different from that of wild strains, but its growth rate was slowed down, moreover, the hyaline circle formed by the mutant strain ΔPL5T-1 using pectin was significantly smaller than wild strain, and the deletion of this gene affected the infestation rate of S. galilaeus 5T-1. Our results confirm that the CP966_RS08110 gene was the pathogenic factors and played a key role in process of infecting and causing potato common scab, which laid foundation for understanding the pathogenic mechanism of S. galilaeus 5T-1.